Strategic Best Practices for Cloud-Based AI Contact Centers in Healthcare - Padala, Suresh (International Journal of Computing and Engineering, 2025)
The healthcare industry faces mounting pressures to enhance patient communication systems while maintaining nonsupervisory compliance and functional effectiveness. Cloud-grounded artificial intelligence contact centers present transformative results that address traditional limitations in healthcare communication structure through intelligent robotization and advanced decision-making capabilities. Perpetration requires a comprehensive evaluation of pall structure providers grounded on security instruments, compliance fabrics, and healthcare-specific moxie. Intelligent Interactive Voice Response design incorporates substantiation-grounded clinical decision support tools that prioritize patient calls based on medical urgency and perceptivity situations while accommodating different case populations, including senior cases, non-native speakers, and individuals with disabilities. Regulatory compliance fabrics encompass multi-layered security infrastructures with specialized, executive, and physical safeguards that cover patient health information in palliative surroundings. Performance optimization strategies concentrate on essential criteria, including first-call resolution rates, artificial intelligence routing accuracy, and patient satisfaction scores through nonstop monitoring and iterative enhancement processes. The integration of these factors creates scalable, secure, and biddable results that enhance patient experience while reducing functional costs and perfecting healthcare availability.